Effectiveness of the Educational Program for the Healthy and Well Nourished Child, for changes in knowledge, behaviors, and practices from mothers with children who are younger than one year of age about nutritional safety taken place in the Moyopampa Hea - Ruth Ester Mamani Limachi (2019)
Purpose: To determine the effectiveness of the Educational Program for the healthy and well nourished child, for changes in knowledge, behaviors, and practices from mothers with children who are younger than one year of age about nutritional safety taken place in the Moyopampa Health Center in Chosica, Lima, (Peru) in 2008.Methodology: The Model of Planning and Programming PROCEDE/PRECEDE was applied, whichwas used in promotion and education programs about health that contemplates five diagnosis: social, epidemiological, environmental and behaviors, educational and organizational, administrative and policies.The design used for the application of the educational program was quasi-experimental worked intwo groups: experimental group (n: 22, whom received the intervention leading to knowledge, behavior,and practices modification in mothers about nutritional safety); and the control group (n: 22, withoutintervention).Results: The experimental group achieved to increment its knowledge level from an averageof 7.1 to a 16.4, in comparison to a control group which moved from 7.2 to 7.6 (P<0.05). As for thebehavior level the experimental group presented an increment from a 4.9 to an 8.3, respectively thecontrol group went from 5.8 diminishing to a 0.7, (P<0.05), the practices about nutritional safety fromthe experimental group showed a 4.6 to a 14.0, while the control group showed an average of 4.6 toa 6.0, (P<0.05).The results of the observation guide in the experimental group showed 37.5% of mothers with a regular practice, 62.5% with a good practice, after the intervention; 20% of the mothers had a good practice,and 80% had a very good practice in the usage of exclusive breast feeding; in the same way the resultsabout complementary feeding before the intervention showed an 83.3% of mother with regular practices,16.7% with good practices; after the intervention 41% had good practices and 53% had very good practices, which reflects an improvement in the practices about nutritional safety.Conclusion: The intervention program for the healthy and well nourished child was effective because it generated a significant impact in the increment of knowledge, behavior modification, and thestrengthening of practices in mothers with children one year and under about nutritional safety taking inaccount the experimental group in relationship to the control group of mothers who were not intervenedby the program.